1988
DOI: 10.1111/j.1751-1097.1988.tb02870.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Photodynamic Action by Rose Bengal in Gram‐positive and Gram‐negative Bacteria

Abstract: Abskact-The photodynamic inactivation by illuminated Rose Bengal of a number of bacterial species was compared. The gram-positive species, Bacillus subtilis, Staphylococcus nureus, Streptococcus faecalis and Streptococcus salivarius, were inactivated about 200X more quickly (99% inactivation) than a Salmonella typhimurium wildtype strain. The Salmonella inactivation curve exhibited an initial lag time during which bacteria were not significantly inactivated. The lag time for inactivation of a derivative of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
2
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 21 publications
1
38
2
3
Order By: Relevance
“…The use of free RB solution in photodynamic inactivation of a number of bacterial species had long been reported in the literature [23, 34]. It was found that some gram-positive bacteria ( Bacillus subtilis , S. aureus , Streptococcus faecalis and Streptococcus salivarius ) were inactivated by free RB dye ~200 times more quickly than the gram-negative Salmonella typhimurium .…”
Section: Resultsmentioning
confidence: 99%
“…The use of free RB solution in photodynamic inactivation of a number of bacterial species had long been reported in the literature [23, 34]. It was found that some gram-positive bacteria ( Bacillus subtilis , S. aureus , Streptococcus faecalis and Streptococcus salivarius ) were inactivated by free RB dye ~200 times more quickly than the gram-negative Salmonella typhimurium .…”
Section: Resultsmentioning
confidence: 99%
“…In Gram‐negative bacteria, the additional outer membrane may confer some protection against exogenous photoinactivation (Dahl et al . ; Mamone et al . ) that the Gram‐positive bacteria do not have.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters could have included such variables as membrane structure, DNA and other cellular repair systems, and levels of antioxidant enzymes. RB and light probably kill bacteria by generating extracellular singlet oxygen that destroys the membrane from the outside in (7,8,33), while polycationic polymeric pL-c e6 is probably taken up into bacterial cells by a self-promoted uptake pathway, as described for other polycationic peptides (24). The finding that uptake levels of both MB and TBO by the NorA knockout mutant, wild-type, and overexpressing strains of S. aureus were proportional to levels of NorA expression suggests that the role of the MDRs is to pump out the PS from the cells and thereby lessen the phototoxicity observed upon illumination.…”
Section: Discussionmentioning
confidence: 99%